Central Station - Salles, Walter; Cohn, Arthur, 1928-; Carneiro, Joô Emanuel; Bernstein, Marcos, 1970-; Clermont-Tonnerre, Martine de.; Montenegro, Fernanda; Pr̊a, Marl̕ia.; Oliveira, Vinc̕ius de.; Sony Pictures Classics (Firm); Mact Productions; VideoFilmes (Firm); RIOFILME (Organization); et al. (Culver City, Calif. : Columbia TriStar Home Video, 1999)
When a young boy witnesses his mother's accidental death, a lonely, retired school-teacher reluctantly takes the child under her wing.
Special features: Audio commentary by Authur Cohn (producer), Fernanda Montenegro (lead actress) and Walter Salles (director) ; theatrical trailer ; talent biographies & filmographies (Walter Salles, Fernanda Montenegro, Marilia Pera, Vinicius de Oliveira).
Originally released in 1998.
Director of photography, Walter Carvalho ; editors, Isabella Rathery, Felipe Lacorda ; music, Antonio Pinto, Jaques Morelembaum.
Fernanda Montenegro, Marl̕ia Pr̊a, Vinc̕ius de Oliveira.
DVD, NTSC, region 1; widescreen presentation ; Dolbly Digital stereo.
Portuguese language soundtrack (stereo) with English subtitles ; closed-captioned in English.
Golden Globe: Best foreign language film.
Keywords: Homeless children -- Brazil -- Rio de Janeiro -- Drama; Homeless children -- Travel -- Brazil -- Drama; Retired teachers -- Brazil -- Rio de Janeiro -- Drama; Retired teachers -- Travel -- Brazil -- Drama; Railroad stations -- Brazil -- Rio de Janeiro -- Drama; Rio de Janeiro (Brazil) -- Drama; Feature films; Fiction films; Films for the hearing impaired